Analysis of Intergenerational Policy Models - Andrzej Klimczuk (Ad Alta: Journal of Interdisciplinary Research, 2013)
Contemporary demographic processes forcing increasing attention to the problems of relationships and dependencies between the different age groups. The ageing of the population in each society leads to changes in the contacts between young people, adults and the elderly. It is reasonable to undertake research on the concept of "solidarity of generations". Maintaining relationships without generational conflict requires actions in the field of social policy known as intergenerational policy. Aim of this article is to present some of its models, which allow not only to analyze the changes in the various communities, but also to create recommendations for public intervention. Description will include activities at the international, national, regional and local levels.
Keywords: J14; J18; Z13; 330; Policy Analysis; Strategic Management; Society for All Ages; Intergenerational programmes; Ageing; Demography; Social policy; Gerontology